High frequency and duration of social media exposure during the COVID- 19 pandemic are associated with mental health problems among employees at an Egyptian university - Ghada O. Wassif; Mohamed Y. El-Awady; Mariam W. Nagi; Isis M. Mossad (Journal of the Egyptian Public Health Association)
Abstract Background The COVID-19 pandemic posed a significant threat to public health, particularly mental well-being. Due to the rapid spread of the virus and quarantine restrictions, social media usage increased dramatically. Excessive and unregulated social media use may negatively impact mental health, contributing to heightened feelings of helplessness and anxiety. This study aimed to examine the relationship between the frequency and duration of social media use and symptoms of depression and anxiety among employees at Ain Shams University during the COVID-19 pandemic. Methods A cross-sectional analytical study was conducted over 6 months, from September 1, 2021, to March 31, 2022, among 405 employees at Ain Shams University. A stratified random sampling method was employed in two stages. First, the university’s faculties were categorized into four disciplines: humanities and social sciences, natural sciences, mathematics, statistics, computer science and engineering, and medical and health sciences. Second, two faculties were randomly selected from each discipline to ensure representative sampling. Data were collected using a structured questionnaire, which included the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9) scales to assess anxiety and depression levels. Results A total of 405 participants were enrolled, comprising 203 males and 202 females, with a mean age of 42.15 ± 10.72 years (range: 20.00–59.00). The majority (77%) held a university degree, and 68.9% were married. A history of COVID-19 infection was reported by 38.3% of participants, and 78.8% used social media to stay updated about the pandemic. Approximately, half of the participants accessed social media three to four times per day, spending an average of 2 to 3 h daily. According to the PHQ-9 scale, 40.7% of employees who accessed social media six or more times per day experienced severe depression symptoms. Similarly, based on the GAD-7 scale, 41.6% of employees who accessed social media six or more times daily reported severe anxiety symptoms. Conclusion The findings suggest a concerning association between frequent COVID-19-related social media exposure and symptoms of depression and anxiety. These results highlight the potential mental health risks associated with excessive social media use, emphasizing the need for mental health awareness programs and strategies to combat misinformation during crises.